New Labour, 'Sleaze' and Television Drama. (18th September 2012) - Fielding, Steven
<x xml:space="preserve">Abstract</x> Research Highlights and Abstract The article explores attitudes to New Labour in particular and politics in general through analysing their dramatization on TV. It indicates that such dramatizations are almost wholly negative, focusing on sleaze, spin and betrayal. The article explains the character of such dramas as being the result of the producers′ desire to present politics in terms their audiences will accept. It suggests that, as a consequence, popular hostility to politics is reinforced by television drama and so indicates that culture has an independent part to play in this process. Echoing Plato's banishment of artists, mainstream political scientists have excluded serious consideration of art from their discipline. Yet, there are grounds for believing that it can help address what Gerry Stoker suggests is one of social science's greatest failings: understanding 'what politics means to citizens'. This study of New Labour's television dramatization suggests it can help political scientists better appreciate the dynamics underpinning the much‐noted decline of popular trust in representative politics. It looks at the reasons for the narrowing of the public's picture of politics by focusing on the changing production context for television drama during the New Labour period, something that led it to emphasise 'sleaze'. The article suggests such dramas consequently helped make more credible the public's pre‐existing prejudices about what they supposed was the corrupt nature of Britain's political class.